Advanced MRI Measures of Cerebral Perfusion and Their Clinical Applications. Issue 2 (April 2017) - Lanzman, Bryan; Heit, Jeremy J.
Abstract : Abstract: Cerebral blood flow measurement by magnetic resonance imaging perfusion (MRP) techniques is broadly applied to patients with acute ischemic stroke, vasospasm following aneurysmal subarachnoid hemorrhage, chronic arterial steno-occlusive disease, cervical atherosclerotic disease, and primary brain neoplasms. MRP may be performed using an exogenous tracer, most commonly gadolinium-based intravenous contrast, or an endogenous tracer, such as arterial spin labeling (ASL) or intravoxel incoherent motion (IVIM). Here, we review the technical basis of commonly performed MRP techniques, the interpretation of MRP imaging maps, and how MRP provides valuable clinical information in the triage of patients with cerebral disease.